Proceso de atención nutricional en paciente masculino de 55 años con enfermedad renal crónica estadío 5. - Villares Sánchez, Ángelo Ronaldo (2024)
Introduction: Chronic kidney disease is a disease that worldwide is considered a public health problem, whose care must be interdisciplinary and the nutritional and dietary therapeutic approach plays a relevant role in halting its accelerated progression and its complications. The general objective of this case study is to carry out the nutritional care process in a 55-year-old male patient with stage 5 chronic kidney disease. The methodology used was to collect quantitative and qualitative information on the patient at the Liborio Panchana Hospital in order to carry out the relevant assessments. As a result of these data, a nutritional diagnosis, intervention and the necessary follow-up were formulated. Thus, it was concluded that chronic kidney disease is a complex pathology that often leads to other health problems such as anaemia, hypertensive crises, concomitant diseases such as diabetes, and therefore, the nutritional approach is crucial. Because of this, teamwork is recommended in order to improve the consequences of the disease itself in a timely and effective manner with the aim of improving the patient's quality of life.